Analisis Framing Terhadap Konten Dakwah Husein Jafar Al Hadar dalam Channel Youtube Jeda Nulis Tentang Toleransi Beragama - Albifaz Arasy Gunawan; Rodliyah Khuza’i (UNISBA Press, 2024)
Abstract. Islam is a proselytizing religion that encourages individuals and groups toward righteousness. In this digital era, many preachers use social media to convey their messages. Husein Jafar is one such preacher who uses YouTube to spread his messages, one of which is the message of religious tolerance. The message of religious tolerance is important to be conveyed in the heterogeneous society of Indonesia. The aim of this research is to understand how Husein Jafar frames his messages of religious tolerance delivered through the YouTube channel